EVALUATION OF ERYTHROCYTES TOXICITY AND ANTIOXIDANT ACTIVITY OF ALKALOIDS OF FUMARIA CAPREOLATA - BRIBI NOUREDDINE; BOUGUEZZA YACINE; MAIZA-BENABDESSELAM FADILA (International Journal of Pharma and Bio Sciences, 2013)
Objective of the present work was to evaluate alkaloids extract of Fumaria capreolata for possible toxicity and antioxidant potential. Antioxidant activity was measured using the 2, 2 0-azino-bis (3-ethylbenzothiazoline-6-sulfonic acid) (ABTS) and the 2, 2-diphenyl-1-picrylhydrazyl (DPPH) scavenging. The significant correlations exist between extract concentrations and percentage scavenging activity of radicals in all models. These results clearly indicate that the alkaloid extract from Fumaria capreolata is effective free radical scavenger and chain breaking antioxidant. In order to assess the toxicity of the alkaloids extract, acute and cell toxicological studies were carried out in mice and erythrocytes. After acute administration of doses 200, 1000 and 2000 mg/kg of total alkaloids, there were no remarkable changes in general appearance and no deaths occurred in any experimental group in both sexes.